Keeping ethnomusical traditions of tatar-chats in modern conditions - A. Martynova, Yulia (2018)
At present, Tatar ethnic linguistics seeks to view Tatar musical culture as a synthesis of regional-dialectological components of various ethnographic and local-territorial groups, which inevitably determines the perception of Tatar musical folklore as a heterogeneous phenomenon. Of particular interest to researchers today is the little-studied traditional culture of the Siberian Tatars. The Siberian Tatars consist of three ethnographic groups, differing from each other by some peculiarities in the spoken language, spheres of material and spiritual culture, lifestyle and everyday life. These are the Tomsk, Baraba, Tobol-Irtysh Tatars, which, in turn, are also divided into subgroups. The names of groups of Siberian Tatars accepted in the literature are associated with the place of their permanent residence. The article discusses the features and problems of preserving the ethno-music culture of one of the dialectal groups of Tomsk Tatars - Ob chats living in the villages of Yurt-Ora and Yurt-Akbalyk, Novosibirsk Region of Russia. Expeditionary research from different years shows that Ob folk music is a diverse phenomenon. There are samples of village song folklore, children's folklore, drawing, lyrical and short songs, takmaks, chastushkas, ceremonial, wedding tunes, singing reading genres, baits and munadjats that are still in the memory of older and middle-aged people. During the 20th century, the musical traditions of the Siberian Tatars were strongly influenced by the cultures of the Volga-Ural Tatars and settlers, which also influenced the stylistic and genre diversity of the region's musical and song folklore. The study of the inexhaustible wealth of the musical folklore of the Tatars of the Novosibirsk Region will allow preserving for subsequent generations the distinctive and universal foundations of the spiritual culture of the entire Tatar people.